2011 26th IEEE/ACM International Conference on Automated Software Engineering (ASE 2011) 2011
DOI: 10.1109/ase.2011.6100056
|View full text |Cite
|
Sign up to set email alerts
|

Localizing SQL faults in database applications

Abstract: Abstract-This paper presents a new fault-localization technique designed for applications that interact with a relational database. The technique uses dynamic information specific to the application's database, such as Structured Query Language (SQL) commands, to provide a fault-location diagnosis. By creating statement-SQL tuples and calculating their suspiciousness, the presented method lets the developer identify the database commands and the program statements likely to cause the failures. The technique al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…We plan to incorporate techniques that generate more readable and realistic data values [31], [32], [33], [34], thus helping humans understand test cases more easily [17], [35]. We will also integrate the tool with others that support software maintenance activities like regression testing [36] and fault localization [37]. Next, we will extend the tool so that it enables the testing of recently developed NoSQL systems.…”
Section: Discussionmentioning
confidence: 99%
“…We plan to incorporate techniques that generate more readable and realistic data values [31], [32], [33], [34], thus helping humans understand test cases more easily [17], [35]. We will also integrate the tool with others that support software maintenance activities like regression testing [36] and fault localization [37]. Next, we will extend the tool so that it enables the testing of recently developed NoSQL systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the fault-based category the existing works range from the development of sets of mutants for SQL queries [17], [18] or schemas [19], [20], [21] to the evaluation of the fault-detection effectiveness with tools [22], [23], [24], [25], fault-localization [26] and empirical studies [27]. Others are application specific, mainly with the goal of detecting SQL injection vulnerabilities [28], [29], [30] and preventing them [31].…”
Section: Test Coverage For Database Applicationsmentioning
confidence: 99%
“…It was reported that there are common failures in a dynamic Web application that are caused by the interaction and passing of data between the application and the database [2]. Many researchers developed automated fault localization methods for traditional, non-database applications [1], [4], [5] and for data-centric applications (i.e.…”
Section: Introductionmentioning
confidence: 99%